Incidence and the risk of occurrence of benign and malignant canine skin tumours in Poland – a five-year retrospective study - Śmiech Anna; Bulak Kamila; Łopuszyński Wojciech; Puła Agata (Journal of Veterinary Research, 2023)
The aim of the study was to compile data on the frequency and distribution of canine skin tumours and determine the risk of these being malignant as opposed to benign. This determination proceeded from tumour histogenesis and gave consideration to the dog’s breed, sex, age and the anatomical location of tumours.